2023
DOI: 10.2147/ijn.s412717
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Immunomodulatory Mechanisms of Mesenchymal Stem Cells-Derived Exosome on Immune Cells in Scar Formation

Abstract: Pathological scars are the result of over-repair and excessive tissue proliferation of the skin injury. It may cause serious dysfunction, resulting in psychological and physiological burdens on the patients. Currently, mesenchymal stem cells-derived exosomes (MSC-Exo) displayed a promising therapeutic effect on wound repair and scar attenuation. But the regulatory mechanisms are opinions vary. In view of inflammation has long been proven as the initial factor of wound healing and scarring, and the unique immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“…For clinical applications, we used a full-thickness cutaneous wound model in diabetic mice, as well as NIH/3T3 fibroblasts, to observe whether the enhanced exosomes had better efficacy. Consistent with previous reports [ 25 , 36 , 37 ], control exosomes from untreated hucMSCs significantly accelerated the wound healing procedure, and our CHIR-Exos were even more effective: compared with control exosomes, CHIR-Exos significantly accelerated the wound healing rate, enhanced local collagen deposition, promoted angiogenesis, and reduced chronic inflammation in diabetic mice. Subsequent in vitro experiments confirmed that the CHIR-Exos promoted wound healing by facilitating cell migration, inhibiting oxidative stress-induced apoptosis, and preventing cell cycle arrest.…”
Section: Resultssupporting
confidence: 92%
“…For clinical applications, we used a full-thickness cutaneous wound model in diabetic mice, as well as NIH/3T3 fibroblasts, to observe whether the enhanced exosomes had better efficacy. Consistent with previous reports [ 25 , 36 , 37 ], control exosomes from untreated hucMSCs significantly accelerated the wound healing procedure, and our CHIR-Exos were even more effective: compared with control exosomes, CHIR-Exos significantly accelerated the wound healing rate, enhanced local collagen deposition, promoted angiogenesis, and reduced chronic inflammation in diabetic mice. Subsequent in vitro experiments confirmed that the CHIR-Exos promoted wound healing by facilitating cell migration, inhibiting oxidative stress-induced apoptosis, and preventing cell cycle arrest.…”
Section: Resultssupporting
confidence: 92%
“…Chronic wounds: long-term, and frequently a consequence of chronic disorders like diabetes [ 21 , 22 ].…”
Section: Wound Processesmentioning
confidence: 99%
“…Zhao W et al used exosomes derived from mesenchymal stem cells (MSC-Exo) to down-regulate the expression of SIRT1 and inhibit the biological behaviors of fibroblasts, thereby directly or indirectly modulating the immune response during pathologic scarring, which can be applied to skin scarring, organ fibrosis, and other related diseases. 207 However, exosome production, isolation, and utilization efficiency remain challenging. Adopting strategies to enhance exosome production and activity is urgent in the current biomedical field.…”
Section: Summary and Prospectsmentioning
confidence: 99%